Perceptions of Garut Business Forum on the Impact of Garut Railway Revitalization - Destty Nurafifah (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2023)
Since 2019, the West Java provincial government has been trying to reactivate the railroad through a revitalization procedure. The program covers several areas, and one of them is Garut. In its undertaking, the revitalization agenda invites various perceptions from the community. Several parties consider that the presence of the train needs to be reviewed. One of the elements that are quite vocal in voicing it is the Chairman of ORGANDA (Organisasi Angkutan Darat) Garut Regency, with the focus of the discussion on changes in community economic governance. Furthermore, the Garut Business Forum was invited to examine this matter and specifically express their perceptions. Based on these findings, researchers aim to determine the Garut Business Forum's perception of the impact of Garut's railroad revitalization. The researcher chose a qualitative research method to find answers to the objectives. Several informants were considered relevant to contribute their thoughts chosen to be interviewed. The informant was the Chairman of ORGANDA Kab. Garut, Academician of STIE Yasa Anggana, Deputy Chairman of Garut, and Chairman of the Garut Business Forum. The research procedures were interviews and processing, assisted by the NVIVO 12 application. After a series of research procedures were carried out, it was concluded that railroad revitalization played a role in encouraging and motivating the movement of economic actors. Then, cooperation with ORGANDA or allied organizations is required to create a successful action. The form of the findings obtained is then explained in full in the article. Keywords: Perception; Revitalization; Train